2017
DOI: 10.3892/mco.2017.1321
|View full text |Cite
|
Sign up to set email alerts
|

Significance of psoas muscle thickness as an indicator of muscle atrophy in patients with hepatocellular carcinoma treated with sorafenib

Abstract: Abstract. Sarcopenia has been reported to be associated with the prognosis of patients with liver cirrhosis and hepatocellular carcinoma (HCC). The aim of the present study was to determine whether sarcopenia was associated with the prognosis of patients with HCC treated with sorafenib. A total of 40 patients with HCC who were treated with sorafenib were evaluated. As an indicator of skeletal muscle mass, transverse psoas muscle thickness (TPMT) was measured on computed tomography images at the level of the um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…Sarcopenia is associated with unfavorable mortality in patients with cirrhosis or HCC, independent of liver function reserves . Patients with HCC receive various treatments along with assessments of both TNM stage and liver function reserves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia is associated with unfavorable mortality in patients with cirrhosis or HCC, independent of liver function reserves . Patients with HCC receive various treatments along with assessments of both TNM stage and liver function reserves.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, skeletal muscle mass decreased by 2.2% per year in patients with liver cirrhosis, and the rate of decrease increased in parallel with the severity of cirrhosis . Sarcopenia has a negative impact on mortality in patients with liver cirrhosis regardless of the presence of hepatocellular carcinoma (HCC) …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Its presence has also been associated with increased toxicity in patients with HCC treated with sorafenib 16 and reduced survival, but the few data available come mainly from oriental series, where ethnic and anthropometric differences limit reproducibility in a Western setting. [17][18][19] Only one Western study is available, with a limited number of patients treated with various tyrosine kinase inhibitors. 20 The aim of the present study was to identify the prevalence and influence of sarcopenia in a homogeneous population of European Caucasian patients with advanced HCC undergoing sorafenib therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the duration of sorafenib treatment is significantly shorter in patients with LSMM than in non‐LSMM patients . In contrast, others did not investigate the therapy duration . These findings indicate that patients with LSMM are more likely to have a shorter duration of sorafenib treatment than non‐LSMM patients; however, previous studies have indicated that LSMM was associated with survival without analyzing the duration of sorafenib treatment with Cox regression analysis.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to skeletal muscle mass loss, intramuscular fat and visceral adiposity independently predicted mortality in patients with various stages of HCC in Japan . Several reports have recently demonstrated that skeletal muscle loss is associated with prognosis in patients with unresectable HCC receiving sorafenib treatment . However, only one report indicated that high visceral fat area (VFA) predicted survival in patients with HCC treated with tyrosine kinase inhibitors .…”
Section: Introductionmentioning
confidence: 99%